1980
DOI: 10.1083/jcb.85.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Purified lectin from skeletal muscle inhibits myotube formation in vitro.

Abstract: A lactose-extractable lectin obtained from 14-16-d embryonic chick pectoral muscle and myotube muscle cultures by affinity chromatography inhibited myotube formation in culture . When applied to muscle cultures at 0 .09 Itg/ml, the purified lectin produced variable effects on the inhibition of myotube formation related to the time and length of application, suggesting that components of the culture medium and/or temperature produced inactivation . Hemagglutination assays showed that the lectin was inactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1982
1982
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…With the exception of the inhibitor of fusion in CEE described by Slater (3), the DI does not appear to correspond to inhibitors of fusion previously described in the literature . Its lack of hemagglutinating activity, as well as its heat and acid stability, contrasts sharply with the lectins studied by several other groups (20)(21)(22)(23)(24). The lectin with properties closest to those we have observed is probably Podleski's "myonectin", but the DI is quite stable to exhaustive dialysis, is relatively heat-stable, and is not inactivated as a result of the loss of a small stabilizing molecule during gel filtration; all of these differ from myonectin (24; T. R. Podleski, personal communication) .…”
Section: Determination Of Mitogenic Activity Of the Differentiation Imentioning
confidence: 73%
“…With the exception of the inhibitor of fusion in CEE described by Slater (3), the DI does not appear to correspond to inhibitors of fusion previously described in the literature . Its lack of hemagglutinating activity, as well as its heat and acid stability, contrasts sharply with the lectins studied by several other groups (20)(21)(22)(23)(24). The lectin with properties closest to those we have observed is probably Podleski's "myonectin", but the DI is quite stable to exhaustive dialysis, is relatively heat-stable, and is not inactivated as a result of the loss of a small stabilizing molecule during gel filtration; all of these differ from myonectin (24; T. R. Podleski, personal communication) .…”
Section: Determination Of Mitogenic Activity Of the Differentiation Imentioning
confidence: 73%
“…Authors in [26] suggested that a membrane-bound lectin is involved in the fusion of L6 myoblasts; authors in [27] however, found evidence to the contrary in chick embryo myoblasts. Authors in [28] reported that a lectin from chick embryo skeletal muscle is inhibitory to the fusion of myoblasts, but have suggested that it may mediate cell-cell contact. It remains to be investigated whether the recognition of intracellular membranes before their fusion with each other is mediated by membrane-bound lectin-like molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble electronectin activity is regulated by a second protein, myonectin, which also undergoes a transient increase before fusion. Importantly an electronectin-like P-D-galactoside-binding protein has been isolated from chick embryonic muscle (Den & Malinzak, 1977;Nowak et al, 1977;MacBride & Przybylski, 1980). It has been claimed that this endogenous lectin is involved in fusion, since the f-D-galactoside-binding protein has been shown to inhibit fusion in aligned myoblasts (Gartner & Podleski, 1975;MacBride & Przybylski, 1980).…”
Section: Surface Biochemistry Of Myoblasts During Fusionmentioning
confidence: 96%
“…Importantly an electronectin-like P-D-galactoside-binding protein has been isolated from chick embryonic muscle (Den & Malinzak, 1977;Nowak et al, 1977;MacBride & Przybylski, 1980). It has been claimed that this endogenous lectin is involved in fusion, since the f-D-galactoside-binding protein has been shown to inhibit fusion in aligned myoblasts (Gartner & Podleski, 1975;MacBride & Przybylski, 1980). This role has been disputed, however (Den et al, 1976;Kaufman & Lawless, 1980), and Den & Chin (1981) have been unable to detect the lectin on the myoblast cell surface.…”
Section: Surface Biochemistry Of Myoblasts During Fusionmentioning
confidence: 99%